The wrath of Dionysus : a novel - Nagrodskaia, E. (Indiana University Press, 1997)
The Wrath of Dionysus, foregrounding changing gender roles and issues of sexual identity, became a sensational and controversial best-seller soon after it hit Russian bookstores in 1910. Long before postmodernism suggested that gender was a social construct rather than a biological absolute, Nagrodskaia's novel put this issue before middle-class Russian audiences hungry for popular fiction. The novel describes the creative life and romantic entanglements of Tatiana Kuznetsova, an artist who temporarily forsakes her long-term lover and fiance for a sexual affair with an Englishman she meets on a train. Narrated by its heroine, the novel reveals a self-sufficient, emancipated woman struggling to reconcile an artistic career with the demands of love and, eventually, motherhood. Male beauty and homosexual love also figure prominently in this timely tale of gender bending and the search for personal identity.